-5-12+z=3+4z-3+2z

Simple and best practice solution for -5-12+z=3+4z-3+2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-12+z=3+4z-3+2z equation:


Simplifying
-5 + -12 + z = 3 + 4z + -3 + 2z

Combine like terms: -5 + -12 = -17
-17 + z = 3 + 4z + -3 + 2z

Reorder the terms:
-17 + z = 3 + -3 + 4z + 2z

Combine like terms: 3 + -3 = 0
-17 + z = 0 + 4z + 2z
-17 + z = 4z + 2z

Combine like terms: 4z + 2z = 6z
-17 + z = 6z

Solving
-17 + z = 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-17 + z + -6z = 6z + -6z

Combine like terms: z + -6z = -5z
-17 + -5z = 6z + -6z

Combine like terms: 6z + -6z = 0
-17 + -5z = 0

Add '17' to each side of the equation.
-17 + 17 + -5z = 0 + 17

Combine like terms: -17 + 17 = 0
0 + -5z = 0 + 17
-5z = 0 + 17

Combine like terms: 0 + 17 = 17
-5z = 17

Divide each side by '-5'.
z = -3.4

Simplifying
z = -3.4

See similar equations:

| 8/5(-0.6)(5/8) | | =2-4x+4*2+5*3 | | =2-3*9.333+4*2+5*3 | | 4b+3=8b-1+5b | | -6+2m(m+2)=5(5-5m) | | 8x^2+17x-13=23-6x | | =2-3x+4*2+5*3 | | =2-3*1+4*2+5*3 | | 4x=-16(2)+4 | | 0.04x+0.07(9000-x)=540 | | -6-5x=4 | | -6+n=15 | | 2x+6-3=12-4x+3 | | 6=6x-10 | | 15x+6y=35 | | 16x^2-22x=37 | | 3x^2-8x=24 | | 4x+81=x+81 | | 3x^2-5x-6=a | | =75+6*1000 | | -15+8x-3x=7+4x+55 | | 1000=75+6x | | 15x+6y= | | 3xsquared+5x-6=a | | 90/105 | | -12v+19=0 | | -9(-9-p)=12 | | 3(m-z)+5-(2m-z)= | | 3-4x=11+3x-2 | | Y/13=3/17 | | 900=75+6x | | 100=75+6x |

Equations solver categories